2015
DOI: 10.1080/15309576.2015.1006469
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Performance Information Use: Systematic Literature Review and Directions for Future Research

Abstract: The use of performance information in decision-making is a management behavior that has received much attention in public administration research and practice. This article seeks to contribute to a better understanding of this behavior. It conducts a systematic review of 25 recently published empirical studies that have examined drivers of performance information use. Analyzing these studies, which were selected on the basis of their definition of purposeful data use, the article identifies factors that have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
247
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(269 citation statements)
references
References 66 publications
10
247
0
12
Order By: Relevance
“…At a basic level, the administrative role is critical for authorizing the time and resources needed to invest in research, gathering and deploying resources to support evidence retrieval, and identifying agency research needs for programs and initiatives (Birkin, Lee, & Weiner, 2012;McBeath & Austin, in press (Moynihan, Wright, & Pandey, 2012) found that transformational leaders promote evidence use indirectly by facilitating goal clarity (around performance targets and pathways) and by supporting a performance-focused organizational culture. This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011). Research has identified other mechanisms through which agency leaders involve themselves in evidence-informed practice due to the likelihood that they (a) serve as agency representatives for research-based initiatives involving external researchers; (b) are formally responsible for searching for promising practices and identifying evidence-based strategies for responding to current agency dilemmas; (c) oversee data collection and reporting with respect to performance measurement; and (d) organize within-agency communities of learning around professional development and research evidence due to their knowledge of the needs of organizational divisions and key staff (Aarons et al, 2011;Austin et al, 2012;Maynard, 2010).…”
Section: Organizational Factors Promoting Access To Evidencesupporting
confidence: 78%
See 2 more Smart Citations
“…At a basic level, the administrative role is critical for authorizing the time and resources needed to invest in research, gathering and deploying resources to support evidence retrieval, and identifying agency research needs for programs and initiatives (Birkin, Lee, & Weiner, 2012;McBeath & Austin, in press (Moynihan, Wright, & Pandey, 2012) found that transformational leaders promote evidence use indirectly by facilitating goal clarity (around performance targets and pathways) and by supporting a performance-focused organizational culture. This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011). Research has identified other mechanisms through which agency leaders involve themselves in evidence-informed practice due to the likelihood that they (a) serve as agency representatives for research-based initiatives involving external researchers; (b) are formally responsible for searching for promising practices and identifying evidence-based strategies for responding to current agency dilemmas; (c) oversee data collection and reporting with respect to performance measurement; and (d) organize within-agency communities of learning around professional development and research evidence due to their knowledge of the needs of organizational divisions and key staff (Aarons et al, 2011;Austin et al, 2012;Maynard, 2010).…”
Section: Organizational Factors Promoting Access To Evidencesupporting
confidence: 78%
“…In contrast, LeRoux and Wright (2010) found that nonprofit directors rating their organizations highly in the use of performance measures are more likely to suggest that their agencies were making effective strategic decisions. In a systematic review of managerial performance information use, Kroll (2014) concluded that information use is enhanced in the presence of well-designed performance measurement systems (i.e., with clear goals, achievable targets, and face valid and easy to access indicators). These studies suggest the need for further research on the relationship between performance measurement and managerial evidence use.…”
Section: Organizational Factors Promoting Access To Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Performance measurement provides feedback about the efficiency and effectiveness of public service (Kroll, 2015), and is inevitably linked to budgeting decisions, strategic planning, and citizen-government communication in public organizations. Performance budgeting emerges from diffusive innovation to elaborate program evaluation and extends political control over administrative resource allocation.…”
Section: The Application Of Performance Informationmentioning
confidence: 99%
“…A growing body of research has explored how public managers and politicians use performance information and has started to identify antecedents of such use (e.g. Moynihan and Pandey 2010;Van Dooren and Van de Walle 2008;Taylor 2011;Hammerschmid et al 2013a; for a systematic overview, see Kroll 2015). A striking feature of most of this research on performance management is a strong reliance on evidence from Anglo-Saxon countries, Scandinavia and a few other countries, such as the Netherlands, and an absence of empirical research evidence from other countries (for an overview see Boyne 2010b).…”
Section: Introductionmentioning
confidence: 99%